Realtime Life Cycle Assessment, Synthesizing Life Cycle Inventory with Business Process Management, Sustainable Growth in the Fourth Industrial Revolution - Nidhi Gupta; Rohit Singh Lather; Deepal Kumar Bhalla (International Journal of Industrial and Product Design Engineering, 2024)
A prevalent methodology for evaluating the ecological impacts of processes and products throughout their entire life cycle is known as Life Cycle Assessment (LCA). This approach involves scrutinizing each phase, encompassing the extraction of raw materials, manufacturing, utilization, and disposal. Nevertheless, conventional LCA methods often fail to account for the dynamic nature of industrial processes and are deficient in real-time data. The Life Cycle Inventory (LCI), a pivotal component of LCA, demands significant time and energy resources and is predominantly reliant on a substantial corpus of data. Leveraging this extensive dataset not only holds potential for streamlining the LCA process but also for enhancing environmental sustainability initiatives. The aim of this discourse is to introduce and elucidate the application of a Dynamic Life Cycle Assessment (LCA) system, which integrates Business Intelligence (BI) software with an Enterprise Resource Planning (ERP) system. This exposition draws upon a case study involving an Italian ceramic tile factory. The model underwent rigorous validation testing iterations to ensure the integrity of the IT architecture and to analyze both the static and dynamic environmental impacts. The efficacy of the validation procedures was evidenced, establishing the Dynamic LCA system as a valuable tool for evaluating and monitoring the environmental ramifications entwined with production processes.
Keywords: Enterprise resource planning ERP; IOT; Industry 4.0; Life cycle assessment LCA; Real time Data; Sustainable growth; life cycle inventory LCI